Tingkat kunjungan masyarakat pada pelayanan posyandu keluarga di desa Toya, Nusa Tenggara Timur - Hartini Haritani; Sulistia Ardyati; Erma Ewisa Oktresia; Fitriwati Sovia; Muhammad Zainul Majdi; Atiaturrahmaniah Atiaturrahmaniah; Baiq Aryani Novianti (Indonesian Institute For Counseling, Education and Therapy, 2022)
Posyandu cadres are the driving force for the implementation of family posyandu services, both in moving targets, services and reporting. With the changing level of posyandu to a family type of this system increases the workload of posyandu cadres, the competence and skills of cadres need to be improved through training and mentoring. The data obtained was qualitative data with descriptive analysis method. Data collection was carried out by conducting observations, interviews and technical training to posyandu cadres with the aim of providing knowledge about family posyandu services, and basic skills at tables 1 to table 8 for cadres so that the presence of this small group of people could increase the number of targeted visits to posyandu. The results obtained from this activity were: the number of visits by pregnant women, toddlers and the elderly had increased. However, the strategy was needed to increase youth's interest in posyandu according to the number of visits by teenagers.